1976
DOI: 10.1136/vr.99.25-26.498
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of swine dysentery: spirochaetes which may be confused with Treponema hyodysenteriae

Abstract: Spirochaetes, designated PWS, microscopically resembling Treponema hyodysenteriae, were isolated from the colon contents of pigs with post-weaning scours from three herds, which on clinical and epidemiological grounds were thought to be free from swine dysentery. One of the isolates was fed to pigs experimentally but no evidence of disease was noted. Their cultural characteristics differed from those of T hyodysenteriae but they were similar to those of a non-pathogenic spirachaete (4/71) which had been isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

1979
1979
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 0 publications
1
23
1
Order By: Relevance
“…This organism is representative of what was formerly known as the "intermediate types" of B. hyodysenteriae. The pathogenicity of these isolates, now collectively categorized as B. intermedia, has been equivocal in the hands of some researchers; other reports have indicated that these strains are clearly pathogenic but, compared to B. hyodysenteriae, induce a different and milder clinical disease called porcine spirochetal colitis in experimentally infected swine (2,4,8). In the present studies, there was a positive association between the presence of the hlyA betahemolysin gene and pathogenicity in porcine Brachyspira isolates.…”
Section: Fig 1 Chromatogram Of Purified Beta-hemolysincontrasting
confidence: 48%
“…This organism is representative of what was formerly known as the "intermediate types" of B. hyodysenteriae. The pathogenicity of these isolates, now collectively categorized as B. intermedia, has been equivocal in the hands of some researchers; other reports have indicated that these strains are clearly pathogenic but, compared to B. hyodysenteriae, induce a different and milder clinical disease called porcine spirochetal colitis in experimentally infected swine (2,4,8). In the present studies, there was a positive association between the presence of the hlyA betahemolysin gene and pathogenicity in porcine Brachyspira isolates.…”
Section: Fig 1 Chromatogram Of Purified Beta-hemolysincontrasting
confidence: 48%
“…Streptolysin S, which the treponemal haemolysin resembles in several respects, is cytotoxic for leucocytes including lymphocytes, and also for platelets, cell cultures, and erythrocytes (see Jeljaszewicz, Szmigielski and Hryniewicz, 1978). Moreover, it inhibits rosette formation by T lymphocytes Pryjma, 1977, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Strain B78-the type strain of the species T. hyodysenteriae (Harris et al, 1972aFhad undergone at least 100 subcultures (D. L. Harris, personal communication). Strains PWS/B, 4/7 1, PWS/A, and M 1 were intestinal spirochaetes isolated from normal pigs, or pigs with conditions other than swine dysentery (Hudson, Alexander and Lysons, 1976;R. J. Lysons, personal communication), and were known to be serologically distinct from T. hyodysenteriae Burrows, 1979, 1981;Burrows and Lemcke, 1981).…”
Section: Micro-o Rgan Ismsmentioning
confidence: 99%
“…Production of haemolysin by T. hyodysenteriae has been correlated with pathogenicity because nonpathogenic spirochaetes from the porcine intestine are only weakly haemolytic (Hudson et al, 1976;Kinyon et al, 1977;Kinyon and Harris, 1979). However, Hudson et al (1974) showed that T. hyodysenteriae, after 80 passages in vitro, remained haemolytic but was no longer pathogenic for pigs.…”
Section: Introductionmentioning
confidence: 99%